2013
DOI: 10.1016/j.jalz.2013.05.401
|View full text |Cite
|
Sign up to set email alerts
|

P1–178: CSF biomarker variability in the Alzheimer's Association quality control program

Abstract: Background: The cerebrospinal fluid (CSF) biomarkers amyloid beta 1-42, total tau, and phosphorylated tau are used increasingly for Alzheimer's disease (AD) research and patient management. However, there are large variations in biomarker measurements among and within laboratories. Methods: Data from the first nine rounds of the Alzheimer's Association quality control program was used to define the extent and sources of analytical variability. In each round, three CSF samples prepared at the Clinical Neurochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The relationship between random error and overlap between normal and abnormal groups is not specific to AD BBMs but is a general problem throughout the field of clinical chemistry. It has therefore been suggested that the gray zones be defined for diagnostic biomarkers, where biomarker results should be interpreted with caution and need to be confirmed with orthogonal methods 24–25,27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between random error and overlap between normal and abnormal groups is not specific to AD BBMs but is a general problem throughout the field of clinical chemistry. It has therefore been suggested that the gray zones be defined for diagnostic biomarkers, where biomarker results should be interpreted with caution and need to be confirmed with orthogonal methods 24–25,27 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, we primarily considered only one type of error in the present analysis— random error estimated by collecting and analyzing samples from the same individuals at different occasions but within a short time span. Another source of noise that can greatly affect biomarker values is systematic error caused by assay‐related changes in the analytical performance of the methods such as when changing lots of key materials (such as antibodies or calibrators) 27,28 . However, systematic error is much more difficult to quantify empirically given its unpredictable nature.…”
Section: Discussionmentioning
confidence: 99%
“…It took decades for cerebrospinal fluid (CSF) Aβ42 and p-tau to be widely accepted as fluid biomarkers for AD, 20,21 among other reasons due to large variability in levels between and within laboratories. 22,23 Variation has been partially mitigated by fully automated analytical instruments, 24,25 and development of Certified Reference Materials to which commercial assays were recalibrated. 26 Different procedures of sample handling in the pre-analytical phase, from body fluid collection until analysis, also caused variation.…”
Section: Introductionmentioning
confidence: 99%
“…The total allowable error (TAE) of a biomarker, by contrast, is the maximum total error for which a biomarker still performs well in its intended clinical use. 12 While biological/patient-related factors do not appear to pose a significant problem for CSF AD biomarkers, 13,14 pre-analytical (e.g., sample handling and storage) and analytical (e.g., between/within differences in laboratory procedures) variability is known to affect biomarker values from enzyme-linked immunosorbent assays (ELISA), 15 which are widely used for routine CSF biomarker analysis. This has been shown to result in interlaboratory variation up to 15%.…”
Section: Introductionmentioning
confidence: 99%
“…While biological/patient‐related factors do not appear to pose a significant problem for CSF AD biomarkers, 13,14 pre‐analytical (e.g., sample handling and storage) and analytical (e.g., between/within differences in laboratory procedures) variability is known to affect biomarker values from enzyme‐linked immunosorbent assays (ELISA), 15 which are widely used for routine CSF biomarker analysis. This has been shown to result in interlaboratory variation up to 15% 15 . This can be addressed through the use of standardized protocols for CSF collection and storage 16 and fully automated platforms such as the Roche Elecsys immunoassays that have high test–retest reliability (<5%) and low laboratory‐ and kit‐associated variability 13 .…”
Section: Introductionmentioning
confidence: 99%